Making decent work a reality to transgender individuals: A step towards a realization of sustainable development goals in developing countries - Abdul Majid; Muhammad Yasir; Missal Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
The main objective of the study is to determine the scope and importance of the crucial indicators that have positive impact in the provision of decent work (DW) opportunities to transgender individuals. In exploring the dynamics of DW, this study also investigates the important role of social & family support (SFS), career orientation (CO) and career initiatives (CI). Data was gathered from 341 transgender individuals residing in Khyber Pakhtunkhwa, Pakistan. In this study, we used a cross-sectional design and survey method. Moreover, questionnaires were used to collect the data. Statistical techniques like regression and structural equation modelling (SEM) were applied to analyze the data by making use of SPSS and AMOS. Findings of the study support a positive predictive association of SFS, CO, and CI with DW, therefore, this emphasizes their relevance in shaping DW among transgender individuals. The findings of the study demonstrate that CI mediates the associations between SFS and DW, and CO and DW. The outcomes of this research indicate that SFS, CO, and CI have a significant role in ensuring DW role. Through focusing on the mediating mechanism in which CO, SFS and CI are important predictors, this study is first of its kind in the context of developing countries that attempts to present a solid framework that would be helpful in providing decent work opportunities to underprivileged class of the society especially transgender individuals residing in developing countries.
Keywords: 330; Decent work; career orientation; social & family support; career initiatives; transgender; Pakistan